Pelaksanaan Sistem Full Day School (Study Kasus Di SD Islam Mumtaz Cidahu Kuningan Jawa Barat) - Rima Melati (Oasis : Jurnal Ilmiah Kajian Islam, 2019)
Islamic Elementary School of Mumtaz has implemented a full day learning system since 2014. This research is a manifestation of the researchers' curiosity about the full day school system at Mumtaz Islamic Elementary School. This study used a qualitative approach, the location of his research at Mumtaz Cidahu Islamic Elementary School, Kuningan, West Java. Data collection techniques with observation, in-depth interviews, and documentation analysis. Islamic Elementary School of Mumtaz  includes having two integrated curricula, the Ministry of Education and Culture curriculum and the Imam Nawawi foundation curriculum in Islamic education (tauhid, morality, jurisprudence, dzikir do'a, hifdzul hadith, al-quran, tahfidz quran and Arabic reading). The learning method is made easy fun. The implementation of a full day school system at Mumtaz Islamic Elementary School in Islamic education subjects has been successful, as seen from the grades of the class above 83, the attitude of the students who are better, memorization, the achievements of the race and the number of students who continue to increase Sekolah Dasar Islam Mumtaz  melaksanakan sistem full day school sejak tahun 2014. Penelitian ini adalah wujud  dari rasa keingintahuan  peneliti akan  pelaksanaan sistem full day school di SD Islam Mumtaz. Penelitian ini menggunakan  pendekatan kualitatif, lokasi penelitiannya di SD Islam Mumtaz Cidahu Kuningan Jawa Barat. Teknik pengumpulan data dengan observasi, wawancara mendalam, serta analisis dokumentasi. Kurikulum SD Islam Mumtaz yaitu kurikulum kemendikbud dan kurikulum yayasan Imam Nawawi  di mata pelajaran PAI (tauhid, akhlak, fiqih, dzikir do’a, hifdzul hadits, al-qur’an, halaqoh, tahfidz quran dan membaca arab gundul). Metode pembelajaranya dibuat  mudah  menyenangkan. Pelaksanaan sistem full day school  di  SD Islam Mumtaz pada mata Pelajaran Pendidikan Agama Islam sudah berhasil, terihat dari nilai raport rata rata kelas di atas 83, sikap siswanya yang lebih baik, hafalan,  prestasi hasil perlombaan serta jumlah siswanya yang terus meningkat